"Sri Aurobindo; The Mother, with Letters on the Mother" (Pondicherry, 2002)
Contains Sri Aurobindo's writing "The Mother" plus his answers on numerous aspects of the Mother's work and powers. The Mother and the working of the Ashram. Also Aspects and powers along with Lights and Visions of the Mother.
Keywords: Yoga